2015
DOI: 10.5812/atr.30244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safe Ischemic Time of Clamping During Intermittent Pringles Maneuver in Rabbits

Abstract: Background:The liver is the most commonly injured organ in blunt abdominal trauma. Although major hepatic bleeding may be partially controlled with portal triade clamping (the Pringle’s maneuver), continuous prolonged clamping results in liver ischemia.Objectives:The purpose of this study was to determine the safe time of Pringle maneuver based on pathologic changes of liver in rabbit models.Materials and Methods:In an experimental study, 20 New-Zealand white rabbits were selected. In laparotomy, a blunt disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In a previous study, the appropriate clamping time and declamping time for the Pringle maneuver were reported [29]. Another report concluded that 30 min is an appropriate clamping time to protect against ischemic injury and suggested a reperfusion time of 5 min [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the appropriate clamping time and declamping time for the Pringle maneuver were reported [29]. Another report concluded that 30 min is an appropriate clamping time to protect against ischemic injury and suggested a reperfusion time of 5 min [30].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of continuous clamping can be up to 90 minutes in the absence of liver pathology or up to 50 minutes in the presence of liver disease (13). Kolahdoozan et al demonstrated in experiments on animals that the safe time interval for clamping the PT was 30-45 minutes (average) (14).…”
Section: Introductionmentioning
confidence: 99%